Indonesia dalam Pertautan Budaya Pembangunan dan Budaya Warga Desa - Agusta, Ivanovich (UI Scholars Hub, 2007)
The construction of the next imagined-village as a part of the next imagined-Indonesia evokes the need of a new genre on embedding the culture of development and the culture of civil-village. The article presents an